2017
DOI: 10.1136/bmjopen-2016-014549
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of vitreous specimens for uveitis classification: a prospective multicentre observational study

Abstract: PurposeTo determine the clinical relevance of vitreous biomarkers in patients with uveitis.DesignMulticentre, prospective, observational study.SettingUveitis outpatient clinics of two academic medical centres in Japan.Patient populationThis study included 234 eyes of 191 patients with various uveitis aetiologies: definitive sarcoidosis (61 eyes of 46 patients), suspected sarcoidosis (60 eyes of 45 patients), intraocular tumour (34 eyes of 27 patients), viral infection (20 eyes of 18 patients), non-sarcoidosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, it is worth noticing that the CD4/CD8 ratio in the vitreous fluid showed high sensitivity (100%) and specificity (96.3%) for the diagnosis of ocular sarcoidosis in one study [ 117 ]. Another multicenter, prospective study confirmed that vitreous CD4/CD8 or CD4 + measurements are higher in ocular sarcoidosis than in other uveitis etiologies [ 118 ].…”
Section: Diagnostic Modalitiesmentioning
confidence: 93%
“…However, it is worth noticing that the CD4/CD8 ratio in the vitreous fluid showed high sensitivity (100%) and specificity (96.3%) for the diagnosis of ocular sarcoidosis in one study [ 117 ]. Another multicenter, prospective study confirmed that vitreous CD4/CD8 or CD4 + measurements are higher in ocular sarcoidosis than in other uveitis etiologies [ 118 ].…”
Section: Diagnostic Modalitiesmentioning
confidence: 93%